Achilles Tendon Repair by Decellularized and Engineered Xenografts in a Rabbit Model. (29th August 2019) - Bottagisio, Marta; D'Arrigo, Daniele; Talò, Giuseppe; Bongio, Matilde; Ferroni, Marco; Boschetti, Federica; Moretti, Matteo; Lovati, Arianna B.
Abstract : Tendon tissue ruptures often require the replacement of damaged tissues. The use of auto- or allografts is notoriously limited due to the scarce supply and the high risks of immune adverse reactions. To overcome these limitations, tissue engineering (TE) has been considered a promising approach. Among several biomaterials, decellularized xenografts are available in large quantity and could represent a possible solution for tendon reconstruction. The present study is aimed at evaluating TE xenografts in Achilles tendon defects. Specifically, the ability to enhance the biomechanical functionality, while improving the graft interaction with the host, was tested. The combination of decellularized equine-derived tendon xenografts with or without the matrix repopulation with autologous bone marrow mesenchymal stem cells (BMSCs) under stretch-perfusion dynamic conditions might improve the side-to-side tendon reconstruction. Thirty-six New Zealand rabbits were used to create 2 cm long segmental defects of the Achilles tendon. Then, animals were implanted with autograft (AG) as the gold standard control, decellularized graft (DG), or in vitro tissue-engineered graft (TEG) and evaluated postoperatively at 12 weeks. After sacrifice, histological, immunohistochemical, biochemical, and biomechanical analyses were performed along with the matrix metalloproteinases. The results demonstrated the beneficial role of undifferentiated BMSCs loaded within decellularized xenografts undergoing a stretch-perfusion culture as an immunomodulatory weapon reducing the inflammatory process. Interestingly, AG and TEG groups exhibited similar results, behaved similarly, and showed a significant superior tissue healing compared to DG in terms of newly formed collagen fibres and biomechanical parameters. Whereas, DG demonstrated a massive inflammatory and giant cell response associated with graft destruction and necrosis, absence of type I and III collagen, and a higher amount of proteoglycans and MMP-2, thus unfavourably affecting the biomechanical response. In conclusion, this in vivo study suggests a potential use of the proposed tissue-engineered constructs for tendon reconstruction.